Melampaui Ritual: Tribuana Manggala Bhakti sebagai Ruang Perjumpaan Lintas Agama di Kulon Progo - M Naufal Firosa Ahda; Amalia Hamida, Nur (LP2M UIN Sunan Kalijaga, 2023)
Interreligious dialogue is still often characterised as a form of dialogue that is ideally organised formally and represented by religious leaders, elites, and government officials. Dialogue, which tends to be rigid and limit access to most of the community, is a challenge in the context of interreligious dialogue in presenting a more inclusive space that allows for broader community involvement. This research aims to explore interreligious relations through the Tribuana Manggala Bhakti tradition in the Jatimulyo Village community, Kulon Progo, Yogyakarta Special Region. A qualitative research method with a case study approach was used as a tool for obtaining data in the field. The subjects in this study amounted to four people who came from among residents, interfaith youth, religious leaders, and community leaders. The results of the study show that the Tribuana Manggala Bhakti tradition has transformed its meaning from a symbol of Buddhist tradition to a social symbol of society in general, so that it goes beyond its functions as a ritual. The shift in meaning in the tradition is due to several factors, namely: the support of the village government, having local wisdom values that are relevant to community life, and the emergence of enthusiasm and community participation in the success of the event. The challenges currently faced are related to the participation of the village youth, who are gradually decreasing in their participation to maintain and be involved, so that in the future, the tradition requires the role of youth on an ongoing basis in an effort to maintain that the space for interfaith encounters still exists in Jatimulyo Village. [Dialog lintas agama masih sering dipahami sebagai suatu cara yang idealnya dilakukan secara formal dan diwakili oleh para pemuka agama dan pejabat pemerintah. Dialog yang cenderung kaku dan membatasi akses sebagian besar masyarakat, menjadi tantangan tersendiri pada konteks dialog lintas agama dalam menghadirkan ruang yang lebih inklusif serta memungkinkan keterlibatan masyarakat secara luas. Penelitian ini bertujuan mengkaji bagaimana tradisi Tribuana Manggala Bhakti muncul dan bertransformasi menjadi kegiatan serta ruang perjumpaan lintas agama masyasrakat Desa Jatimulyo. Metode penelitian kualitatif dengan pendekatan studi kasus digunakan sebagai alat dalam mendapatkan data di lapangan. Subjek dalam penelitian ini berjumlah empat orang yang berasal dari kalangan warga, pemuda lintas agama, tokoh agama, dan tokoh masyarakat. Hasil studi menunjukkan bahwa tradisi Tribuana Manggala Bhakti mengalami pergeseran makna, dari simbol tradisi warga agama Buddha ke simbol sosial masyarakat secara umum. Bergesernya makna dalam tradisi tersebut dikarenakan beberapa faktor yakni: adanya dukungan dari kalangan pemerintah desa, memiliki nilai-nilai kearifan lokal yang relevan dengan kehidupan masyarakat, dan munculnya antusias serta keikutsertaan masyarakat dalam menyukseskan acara tersebut. Adapun tantangan yang saat ini dihadapi terkait denganadalah soal keikutsertaan para pemuda desa yang lambat laun mengalami penurunan dalam partisipasinya untuk merawat dan terlibat, sehingga kedepannya tradisi tersebut memerlukan peran pemuda secara berkelanjutan dalam upaya menjaga agar ruang perjumpaan lintas agama masih tetap ada di Desa Jatimulyo]